2006
DOI: 10.1186/cc4992
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin level and leukocyte antisedimentation rate as early predictors of respiratory dysfunction after oesophageal tumour resection

Abstract: Introduction Postoperative care after oesophageal tumour resection holds a high risk of respiratory complications. We therefore aimed to determine the value of systemic inflammatory markers in predicting arterial hypoxaemia as the earliest sign of developing lung injury after oesophageal tumour resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Plasma PCT levels have been studied and compared with CRP in patients after major surgery and trauma, but the results are inconclusive. 14 18 , 20 So far, one study on post-esophagectomy showed a diagnostic value of PCT for development of sepsis 11 and another one for infectious complications. 13 We found an early diagnostic value of day 3 PCT levels for combined surgical/infectious complications presenting between days 3 and 10 independently from preoperative risk assessment scores, but not of infectious complications alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma PCT levels have been studied and compared with CRP in patients after major surgery and trauma, but the results are inconclusive. 14 18 , 20 So far, one study on post-esophagectomy showed a diagnostic value of PCT for development of sepsis 11 and another one for infectious complications. 13 We found an early diagnostic value of day 3 PCT levels for combined surgical/infectious complications presenting between days 3 and 10 independently from preoperative risk assessment scores, but not of infectious complications alone.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 8 10 , 12 , 13 PCT is an allegedly more specific marker of severe infection and complications after surgery than CRP, 14 16 but the literature is inconclusive in this respect. 17 , 18 So far, only five studies reported on PCT levels post-esophagectomy, 1 , 11 , 13 , 19 , 20 of which only two focused on post-operative infectious complications. 11 , 13 The latter studies suggested that PCT is useful for the diagnosis of infectious complications and discriminating sepsis from SIRS post-esophagectomy.…”
Section: Introductionmentioning
confidence: 99%
“…PCT is a specific marker of bacterial infection and has been reported as a predictor of postoperative infectious complications after esophagectomy [ 9 , 10 , 11 , 12 ]. We hypothesized that PCT is a predictor of infectious complications after esophagectomy, and of long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies on blood biophysical properties including viscosity, [1][2][3][4][5][6] viscoelasticity, [7][8][9][10][11][12] deformability, [13][14][15][16][17][18] aggregation, [19][20][21][22] and erythrocyte sedimentation rate (ESR), [23][24][25][26][27] various cardiovascular diseases cause changes in the biophysical properties of the blood. The biophysical properties of the blood have been measured to effectively monitor disease states or their progresses.…”
Section: Introductionmentioning
confidence: 99%